Remediatisation, media interdiscursivity and ideological ambivalence in online news reports on sexual assault. (August 2022) - Lazar, Michelle M.; Wan, Lixin
Abstract: Nowadays, the integration of informal, evaluative and entertaining elements in news production is not an uncommon practice in certain types of news genres. Our focus is on such elements expressed innovatively through image-based digital resources (IDRs) borrowed from participatory internet media culture, which include internet memes, emojis, screenshots of TV dramas/movies and digital archives, in social media news reporting. Our case study deals with news reports about sexual assaults by a Chinese official news outlet People.cn on Sina Weibo, one of the largest social media platforms in mainland China. Using the concepts of 'remediatisation' and 'media interdiscursivity', we unpack the ideological implications of the representation of sexual assaults and the social actors (perpetrators and victims) involved in the cases. Our study shows that the unexpected and innovative use of IDRs by the news media generates particular kinds of affect that result in an ideological ambivalence about sexual assaults and sexual crime reporting.